2015
DOI: 10.1002/jobm.201400942
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of enolase as a collagen‐binding protein in Lactobacillus plantarum

Abstract: Collagen is a target of pathogens for adhesion, colonization, and invasion of host tissue. Probiotic bacteria can mimic the same mechanism as used by the pathogens in the colonization process, expressing cell surface proteins that specifically interact with extracellular matrix component proteins. The capability to bind collagen is expressed by several Lactobacillus isolates, including some Lactobacillus plantarum strains. In this study we report the involvement of the L. plantarum EnoA1 alfa-enolase in type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 45 publications
3
30
0
1
Order By: Relevance
“…The occurrence of a single bacterial adhesin, interacting with multiple adhesion targets, has been reported for different bacteria . We demonstrated that L. plantarum LM3 EnoA1 is a multi‐functional binding adhesin, being able to interact with CnI and fibronectin . In order to study a putative involvement of the cell surface expressed PDHB in adhesion to different host targets, we performed an adhesion assay to immobilized CnI with the LM3 strain and its isogenic mutant strain LM3‐B1, carrying a null mutation in the pdhB gene .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence of a single bacterial adhesin, interacting with multiple adhesion targets, has been reported for different bacteria . We demonstrated that L. plantarum LM3 EnoA1 is a multi‐functional binding adhesin, being able to interact with CnI and fibronectin . In order to study a putative involvement of the cell surface expressed PDHB in adhesion to different host targets, we performed an adhesion assay to immobilized CnI with the LM3 strain and its isogenic mutant strain LM3‐B1, carrying a null mutation in the pdhB gene .…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, we showed the involvement of the L. plantarum LM3 surface displaced pyruvate dehydrogenase subunit B (PDHB) in fibronectin binding, and of the surface displaced alfa‐enolase (EnoA1) in fibronectin and plasminogen (Plg) binding, identifying also the EnoA1 amino acid residues involved in Plg‐binding . Recently, we also reported the characterization of EnoA1 as a collagen I (CnI) binding adhesin and we identified a region of 67 aa residues involved in CnI‐binding . CnI is the major organic component of the human body and is the target of several pathogens for adhesion and colonization of host tissues .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…4 Mekanisme kerja dari L. plantarum melalui keterlibatan perikatan EnoA1 alfa-enolase pada type I collagen (CnI) binding dan juga melalui memodulasi sistem imun di dalam usus, yang secara langsung maupun tidak langsung mempengaruhi imun sistemik, termasuk imun di kulit. 6,7 Hal ini sangat menarik, terbukti dengan adanya peningkatan penggunaan probiotik topikal oleh masyarakat secara significant yang ditandai dengan mulai beredar produk probiotik topikal di pasaran. Selain itu sejalan dengan telah ditemukan efek positif probiotik topikal untuk terapi dan pencegahan masalah yang timbul pada kulit, seperti penuaan, jerawat, rosasea, infeksi bakteri dan jamur, psoriasis, dan dermatitis.…”
Section: Pendahuluanunclassified